THE EFFECT OF CREDIT RISK, BANK CAPITAL, INDEPENDENT COMMISSIONER, AND AUDIT COMMITTEE ON BANKING FINANCIAL PERFORMANCE IN INDONESIA FOR THE 2017-2021 PERIOD - Shafira Elva Ardelia; Arief Wibisono Lubis (Sean Institute, 2023)
This study examines the effect of credit risk, bank capital, independent commissioner, and audit committee on bank's financial performance. The object of this study is to conventional commercial banks listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The sampling method used to determine the sample is purposive sampling. Data analysis techniques are performed using panel data regression (fixed effect model). The results show that there is a negative significant effect of credit risk on the financial performance of banks calculated using Return on Asset (ROA), and there is no significant effect of credit risk on banking financial performance calculated using Net Interest Margin (NIM). Then there is a positive significant effect of bank capital and independent commissioners on the financial performance of banks calculated using Return on Asset (ROA) and Net Interest Margin (NIM). In addition, there is a positive significant effect of the audit committee on the financial performance of banks calculated using Return on Asset (ROA), and there is no significant effect of the audit committee on the financial performance of banks calculated using Net Interest Margin (NIM). The results of such research can contribute to theoretical and practical fields (banking and financial statement users, especially investors).